ANALISIS PENGENDALIAN INTERNAL DALAM PEMBERIAN KREDIT PADA PT BPR GEMILANG PERSERODA KABUPATEN INDRAGIRI HILIR - Mansyur Mansyur; Novriani Susanti; Ranti Melasari (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2026)
This study aims to analyze the implementation of internal control systems in credit provision at PT BPR Gemilang Perseroda, Indragiri Hilir Regency. Internal control is a crucial instrument for maintaining the effectiveness, efficiency, and compliance of credit procedures, as well as minimizing the risk of non-performing loans. The study employs a qualitative method with a descriptive approach, utilizing primary data through in-depth interviews with relevant personnel and secondary data from the bank’s internal documents. The analysis systematically examines the implementation of internal control components, including control environment, risk assessment, control activities, information and communication, and monitoring. The results indicate that PT BPR Gemilang Perseroda has effectively applied internal control in the areas of control environment, risk assessment, control activities, and information and communication. However, monitoring of credit requires improvement to ensure faster detection of potential credit risks. This study emphasizes that effective internal control not only safeguards credit quality and operational transparency but also enhances customer trust and supports the bank’s financial stability. These findings are significant for credit risk management and improving internal procedures to increase operational efficiency and security in banking.